THE HARMONY AMONG RELIGIONS IN JERUSALEM IN RIDLEY SCOTT’S KINGDOM OF HEAVEN MOVIE (2005): A SOCIOLOGICAL APPROACH - FARCHANI, AZAM (2011)
This study is aimed to show the harmony among religions in jerusalem in kingdom of heaven movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the kingdom of heaven movie directed by Ridley Scott released in 2005. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form solid unity, into good quality of a movie. Second, based on the sociological analysis, there is close relationship between the movie production and the social reality underlying it. This movie reflects the harmony among religions in Jerusalem.